2017
DOI: 10.1371/journal.pone.0172351
|View full text |Cite
|
Sign up to set email alerts
|

Are life-saving anticancer drugs reaching all patients? Patterns and discrepancies of trastuzumab use in the European Union and the USA

Abstract: BackgroundThe development of trastuzumab is considered to be one of the greatest improvements in breast cancer treatment in recent years. This study aims to evaluate changes in the uptake of trastuzumab over the last 12 years and to determine whether its use is proportional to patient needs in the European Union and the USA.MethodsUsing national registry data, the number of new cases of HER2-positive breast cancer patients per year was estimated. The number of likely trastuzumab treatments per year was estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…An additional problem in the case of some Central and Eastern European countries, including Romania, is the lack of access to modern forms of pharmacological therapy for breast cancer [25]. There is still a gap in access to the agents directed against the human epidermal growth factor receptor 2 (anti-HER2 agents) between individual European countries [26]. In most countries of Western Europe, the availability of this form of therapy in 2013 covered its demand, whereas among the countries of Central and Eastern Europe, this condition was only applicable to Slovenia and the Czech Republic.…”
Section: Discussionmentioning
confidence: 99%
“…An additional problem in the case of some Central and Eastern European countries, including Romania, is the lack of access to modern forms of pharmacological therapy for breast cancer [25]. There is still a gap in access to the agents directed against the human epidermal growth factor receptor 2 (anti-HER2 agents) between individual European countries [26]. In most countries of Western Europe, the availability of this form of therapy in 2013 covered its demand, whereas among the countries of Central and Eastern Europe, this condition was only applicable to Slovenia and the Czech Republic.…”
Section: Discussionmentioning
confidence: 99%
“…Actual availability of novel drugs in populations depends on reimbursement policies and was reported as much lower. Ades et al estimated the sizes of populations in need by multiplying country population size, incidence of breast cancer, percentage of human epidermal growth receptor 2 (HER2) positive, number of new such cases, proportion of patients treated in the adjuvant or metastatic setting, and duration of adjuvant and metastatic setting treatment . They found that none of the Eastern European countries achieved the total coverage of the population in need before 2006, when trastuzumab was approved only in the metastatic setting .…”
Section: Discussionmentioning
confidence: 99%
“…Ades et al estimated the sizes of populations in need by multiplying country population size, incidence of breast cancer, percentage of human epidermal growth receptor 2 (HER2) positive, number of new such cases, proportion of patients treated in the adjuvant or metastatic setting, and duration of adjuvant and metastatic setting treatment . They found that none of the Eastern European countries achieved the total coverage of the population in need before 2006, when trastuzumab was approved only in the metastatic setting . After 2006, when trastuzumab was approved in the HER2 positive adjuvant setting, only the Czech Republic and Slovenia achieved total coverage if the incidence of HER2 positive tumor was estimated to 15%.…”
Section: Discussionmentioning
confidence: 99%
“…This leaves only about 5% for the rest of the world. It should not be a surprise that healthcare outcomes clearly correlate with these numbers [6, 12]. As expected, lack of availability and access to anti-HER2 medications has an important impact on outcomes [6, 13].…”
Section: Current Scenario Of Breast Cancer Care In Latin Americamentioning
confidence: 96%
“…In some cases, this reflects patient comorbidities and treatment preference. However, physicians worldwide encounter various barriers to prescribing biologic agents that may also contribute to underuse of anti-HER2 therapy [12] Age, socioeconomic and racial disparities have been demonstrated even in rich countries. A study published in 2015 reported that approximately 50% of patients aged 65 years and older do not receive neoadjuvant or adjuvant treatment with trastuzumab in the USA, especially those with a lower financial income.…”
Section: Barriers To the Incorporation Of New Therapies For Advanced mentioning
confidence: 99%